Analisis Pengaruh Kompetensi Aparatur, Sistem Pengendalian Internal Dan Partisipasi Masyarakat Terhadap Akuntabilitas Pengelolaan Dana Desa Di Desa Nailang Kecamatan Alor Timur Laut Kabupaten Alor - Asamani, Misela; Tang, Sefnat Aristarkus; Sabu, Junius Menase Sau; Maro, Yustina (Jurnal Ilmiah Wahana Pendidikan, 2023)
Accountability is the obligation to provide responsibility or answer and explain the performance and actions of a person leading an organizational unit to parties who have the right or are authorized to ask for accountability. Accountability will be better if it is supported by an accounting system that produces information that is accurate, reliable, timely and accountable (Komang, 2014). In line with this, public accountability is the obligation of stewards (government) to manage resources, report and disclose all activities and activities related to the use of public resources to the mandate giver. This research aims to 1.) determine respondents' perceptions regarding apparatus competency, internal control systems and community participation in the accountability of village fund management in Nailang Village, North East Alor District, Alor Regency. 2.) determine the significance of the simulative (together) influence of community participation, internal control system and community participation in Nailang Village, North East Alor District, Alor Regency. 3.) to find out the significant partial influence of apparatus competency, internal control system and community participation on accountability in managing village funds in Nailang Village, North East Alor District, Alor Regency. The sample in this study was all 72 Nailang village officials and residents. This data collection uses questionnaire techniques, observation, literature study. The data was then analyzed using the t-test to determine the partial effect and the F test to determine the simultaneous effect on accountability in managing village funds. These results show that 1.) the apparatus competency variable has a negative and significant effect on the accountability of village fund management. 2.) The internal control system variable has a negative and significant effect on the accountability of village fund management. 3.) The community participation variable has a negative and significant effect on the accountability of village fund management. 4.) The competence of the apparatus, the internal control system and community participation together (simultaneously) have an influence on the accountability of village fund management.